Transportation of Chemical Materials by Chemical Tankers - Bilen Alkan, Guler; Aydin, Gulsum (Asian Journal of Chemistry, 2010)
This paper provides an overview of the development of the chemical trade and tankers, explains the importance of double hull tankers with the aspect of environmental impact and includes the chemical tanker safety rules and the transportation of chemical materials.